PROSES MANUFAKTUR MESIN PENGIRIS PISANG TIPE PISAU HORIZONTAL BERPENGGERAK MOTOR LISTRIK 0,25 HP - Farizan Nurhanif (2022)
Banana (musa parasidiaca) is one of the leading fruit commodities in Indonesia with a higher amount of production compared to other fruits. The high amount of banana production can be used as a profitable business product, one of which is banana chips. In general, the process of making banana chips is processed conventionally without using a slicing machine, so it takes a long time which can hamper the banana chips production process. The purpose of this research is to obtain a horizontal knife-type banana slicing machine driven by an electric motor of 0.25 HP, to obtain an overview of the manufacturing process for making a banana slicing machine, and to estimate the time and cost needed to manufacture a horizontal knife-type banana slicing machine driven by an electric motor 0. 25 HP. Collecting the required data, drafting a design concept, and manufacturing a banana slicing machine is required to produce a horizontal knife-type banana slicing machine driven by an electric motor of 0.25 HP with a length of 40 cm, a width of 40 cm and a height of 70 cm. The banana slicing machine manufacturing process requires several manufacturing stages, such as: the cutting process, the drilling process, the turning process, the assembly process both permanent (welding) and non-permanent (using nuts and bolts), and the surface finishing process (surface smoothing and painting). The time required to create this machine is 3.78 hours with a total production cost of IDR 2,259,602.60.